Ação rescisória e precedentes: análise dos §§5º e 6º do art. 966 do CPC/2015 - Bizarria, Juliana Carolina Frutuoso (2019)
Presented dissertation analyzes the appropriateness of the action for relief from judgment for manifest violation of the legal norm, proposed in the face of a decision that wrongly applied or failed to apply precedent (art. 966, §5º and §6º). CPC/2015 provides for the action for relief from judgment based on violates a matter adjudged (art. 966, V). The change represents the gradual change in the theory of the sources of law and the evolution of the theory of interpretation by the distinction between text (statement) and norm, overcoming interpretive formalism to conceive of interpretation as an activity of valuation and attribution of meaning. Law nº 13.256/2016 amended CPC/2015 and inserted the possibility of action for relief from judgment against a decision based on a precedent or bench decision in the trial of multiple claims on the same point of law which did not take into consideration the distinction between the matter under analysis in the action and the pattern of decisions on which it was based (§5º of art. 966). The legislative change is justified in view of the adoption of a system of judicial precedents by the CPC, as a way to provide unity, predictability and stability of the law. The aim of this paper is to understand the content, extent and possible repercussions of the modification. To this end, it begins with a comparative study of judicial precedent in common law and the system implemented in Brazil, going through fundamental notions such as ratio decidendi and dictum, techniques related to enforcement and overcoming, as well as the binding pronouncements provided for in the CPC/ 2015. Following, the main aspects of the action for relief from judgment are examined, with emphasis on the analysis of the foundation of art. 966, V (“violates a matter adjudged”). The work is concluded with the examination of §§5º and 6º of art. 966, delimiting the precedents authorizing the invocation of this plea for rescission of the judicial decision, the offense that justifies its use and the temporal limits for its application